Lobster Tales: Narratives of Food, Past, and Place in Maritime Canada - Tye, Diane (Cuizine)

(untitled) (McGill University Library, 2011)
In Canada’s Maritime Provinces, lobster is the food of tourism. Featured in countless guidebooks, cookbooks and restaurant ads, lobster beckons visitors to the region. Later, represented in as many forms as souvenirs, it signifies their trip, offering tangible proof that they have experienced–and tasted–the “real” place. However, as George Lewis (1989) argues is the case in Maine, residents of Prince Edward Island, Nova Scotia and New Brunswick have their own understandings. Here I explore two generalized narratives widespread in Maritime oral tradition: that lobster was used by farmers as fertilizer on fields and that its consumption once was associated with shame, signaling as it did that a family had nothing else to eat. In considering the contested meanings surrounding lobster’s recontextualization from a food of poverty to a regional delicacy, I suggest that Maritimers’ knowledge of lobster’s earlier working class associations, as well as of the “right” way to cook and eat lobster, acts not only as a marker of socio-economic difference but as an indicator of Pierre Bourdieu’s notion of distinction (1984) that is intricately linked to constructions of regional identity.